Theory of machines and mechanisms / John Joseph Uicker; G R Pennock; Joseph Edward Shigley - Shigley, Joseph Edward
Theory of Machines and Mechanisms, Fifth Edition, is an ideal text for the complete study of displacements, velocities, accelerations, and static and dynamic forces required for the proper design of mechanical linkages, cams, and geared systems. The authors present the background, notation, and nomenclature essential for students to understand the various independent technical approaches that exist in the field of mechanisms, kinematics, and dynamics. The fifth edition features streamlined coverage and substantially revised worked examples. This latest edition also includes a greater number of problems, suitable for in-class discussion or homework, at the end of each chapter.